2011
DOI: 10.1371/journal.pone.0016490
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Influencing Morale in the Elderly

Abstract: BackgroundWe examined the relationship between morale measured by the Philadelphia Geriatric Morale Scale (PGC) and disability, social support, religiosity, and personality traits. Instruments predicting morale were then tested against PGC domains.MethodsThe study utilized a cross-sectional survey with a multistage cluster sampling design. Instruments used were disability (disease burden; WHO Disability Score-II, WHODAS-II), social support (Duke Social Support Scale, DUSOCS; Lubben Social Network Scale, LSNS-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Any illness that affects daily activities, social functioning, and well-being can have an important impact (Eriksson et al, 2010) on a person's life (Ellis & Verma, 2000;Wild, Clayson, Keating, & Gondek, 2005;Loke et al, 2011). Chronic illness is one of the common predictors of morale.…”
Section: Chronic Illnessmentioning
confidence: 99%
See 3 more Smart Citations
“…Any illness that affects daily activities, social functioning, and well-being can have an important impact (Eriksson et al, 2010) on a person's life (Ellis & Verma, 2000;Wild, Clayson, Keating, & Gondek, 2005;Loke et al, 2011). Chronic illness is one of the common predictors of morale.…”
Section: Chronic Illnessmentioning
confidence: 99%
“…Chronic illness is one of the common predictors of morale. Loke et al (2011), for their part, identified that the presence of chronic illness shows a clear trend toward low morale. Also, morale has been reported to be influenced by medical conditions such as stroke (Löfgren, Gustafson, & Nyberg, 1999) and Parkinson's disease (Benito-Leon, Louis, & Bermejo-Pareja, 2009).…”
Section: Chronic Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the World Health Organization, social activity and functional independence are the most important determinants of "active aging" [47]. Moreover, Lok et al [48] indicate that disability, social support, religiousness, and the type of the personality have the greatest impact on the health of the elderly, and WHODAS is the best tool to measure the areas of disability.…”
Section: Discussionmentioning
confidence: 99%